The Influence of Microporous Cements on the Pore Network Geometry of Natural Sedimentary Rocks - Thomson, Paul-Ross; Hazel, Alexander; Hier-Majumder, Saswata (Frontiers in Earth Science, 2019)
We investigate the pore network geometry and permeability of six natural sandstones and carbonate rocks. Using 3D microtomographic images, we segment each rock sample into three phases: Solid matrix of grains, macropores containing void spaces, and a third microporous phase containing nanometer-sized pores beyond the resolution of the image. In the majority of our samples, the microporosity exists inside cements deposited as a secondary phase along the surface of grains. Within the macropores, the pore radius, coordination number, throat radius, and throat length display a power law relation with porosity. We also find that the permeability of the aggregate depends on the porosity following the relation k=k0ϕ3.32, where log k0 = 5.52 (mD). The fraction of connected porosity shows a strongly non-linear reduction with an increase in the volume fraction of microporous cement.